Development of a new method of diagnostics electromagnetic drive power and commutation mechanisms - I. V. Bochkarev; I. V. Bryakin (Известия высших учебных заведений: Проблемы энергетики)
A new method for diagnosing power and switching electromagnetic mechanisms containing a control electromagnet and a movable armature is proposed. The movable element of the diagnosed electromagnetic mechanism (EMM) is irradiated with a high-frequency probing electromagnetic field and the reradiated electromagnetic field from it is recorded. The source of the probing field and the receiver of the re-radiated field is the EMM electromagnet winding. The probing electromagnetic field is formed by imposing on the low-frequency high-voltage operating voltage of the supply winding of the electromagnet EMM an additional high-frequency low-voltage voltage. The diagnostic parameter is determined by algorithmic processing of the measurement results of the magnitude of the voltage increment on the EMM winding, caused by exposure to a reradiated electromagnetic field, and the technical condition of the diagnosed electromagnetic mechanism is determined by the absolute value of the di-agnostic parameter. The method allows to diagnose the current state of the main functional units of the EMM and to control its operating modes as a whole.